The limits of normative naturalism - Hambly, Jesse (2020)
Normative judgements - judgements about what we and others ought and have reason to do, believe, intend, and so on - are a ubiquitous and probably inescapable part of our lives. But in virtue of what are such judgement true - if in fact they ever are? Answering this question calls for an account of the nature of normative properties and facts. Normative Naturalists provide such an account, suggesting that normative properties and facts are reducible to natural properties and facts - very roughly, those properties and facts posited by the sciences. In this thesis, I argue that Normative Naturalist views fail; if there are normative properties and facts, it's not the case that they are reducible to natural properties and facts. In Part I of the thesis, I argue against Analytic Normative Naturalist views, which hold that we can establish that normative properties and facts are reducible to natural properties and facts by giving analyses of normative concepts in non-normative terms. The essence of my argument is that Analytic Normative Naturalists can't capture the way normative concepts are supposed to feature in our practices of decision-making, advice and criticism. In Part II, I argue against Non-Analytic Naturalist views, which hold that, while normative properties and facts are reducible to natural properties and facts, normative concepts are not analysable in non-normative terms. I argue that such views can't provide a plausible account of how normative concepts pick out natural properties
Keywords: Hochschulschrift